School Student Responses to Halal Product Labeling - Dwira Eriani, Izmi; Rizki Amalia Elfita (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Inclusion of halal products is one of the important things in the brand considering that most consumers in Indonesia are Muslims. Labeling is an effort to add added value to brands by involving other associations that have the authority to do so, in this case the Halal Product Assurance Organizing Agency (BPJPH) as stipulated in Law Number 33 of 2014 concerning Halal Product Guarantees (JPH). The law emphasizes that products that enter, circulate and trade in Indonesia must be halal certified (Article 4), therefore the government organizes JPH (Article 5). The purpose of this research is to find out the response of school students to the labeling of halal products. This type of research is quantitative research with a survey approach in order to describe the level of response of the school public to halal products, which consists of the level of knowledge, level of concern, and practical attitude responses in addressing matters related to halal products. From the results obtained, there were 66 respondents who were used as samples spread over several SMP/SMA/Universities in East Java Province. Middle school students got the least amount, namely 7 (10.6%), high school students with the highest number, namely 44 (66.7%), and university students with 15 (22.7%). Inclusion of halal products is one of the important things in the brand considering that most consumers in Indonesia are Muslims, not a few Indonesian people when consuming a product no longer pay too much attention to the halalness of a product in Islamic teachings. The urgency of a halal label for Muslim consumers is intended to ensure that any product is which may be consumed. Therefore, Muslim consumers should be careful in deciding to buy or products if the product is not labeled as halal or is not a matter for the consumer himself.